The Cultural Meaning of Ma’kombongan as A Form of Local Wisdom of The Toraja Community - Roberto Salu Situru; Topanus Tulak (Universitas Cokroaminoto Palopo, 2022)
Local wisdom is the originality of an area that distinguishes it from other regions both in terms of meaning and the value it contains. The Toraja tribe, which is located in the province of South Sulawesi, has a strong oral culture so that information is passed down by word of mouth, not in the form of writing or inscriptions. One of the local wisdoms of Toraja culture that is rarely written about is Ma’kombongan . Ma' Kombongan culture as a local wisdom has a strong enough role in the existence of the Tana Toraja people. Ma’kombongan can be said as a form of democratic government of the Toraja people before the current system of government. Therefore, it is important to write articles to see the role of ma’kombongan in creating harmony in Toraja society. This study uses a qualitative research method with data collection through observation and interviews with traditional shops, religious shops, indigenous peoples, and the government. The results of the research illustrate that the ma’kombongan process is carried out in customary areas in various ways such as Rambu solo, rambu tuka', a place to solve problems, resolve conflicts, and as a place for customary justice. The implications of the research provide insight into how important ma’kombongan is in forming harmonization in Toraja society. The research also has implications for the development of social knowledge, especially for creating social integration in society.